1983
DOI: 10.1021/ed060p962
|View full text |Cite
|
Sign up to set email alerts
|

Teaching factor-label method without sleight of hand

Abstract: As an aid in teaching the factor-label method, the author has developed a rather simple card game involving the matching of symbols and colors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While interpreting ratios leads to qualitative understanding and the development of formal reasoning (6,17), dimensional analysis has been advocated by some for students who are concrete reasoners (23,24 ), and it may have merit when students are involved in timed tests in which speed in obtaining a result is important. While interpreting ratios leads to qualitative understanding and the development of formal reasoning (6,17), dimensional analysis has been advocated by some for students who are concrete reasoners (23,24 ), and it may have merit when students are involved in timed tests in which speed in obtaining a result is important.…”
Section: Engaging High School Students In the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While interpreting ratios leads to qualitative understanding and the development of formal reasoning (6,17), dimensional analysis has been advocated by some for students who are concrete reasoners (23,24 ), and it may have merit when students are involved in timed tests in which speed in obtaining a result is important. While interpreting ratios leads to qualitative understanding and the development of formal reasoning (6,17), dimensional analysis has been advocated by some for students who are concrete reasoners (23,24 ), and it may have merit when students are involved in timed tests in which speed in obtaining a result is important.…”
Section: Engaging High School Students In the Methodsmentioning
confidence: 99%
“…These experiences lead to an interesting dilemma. While interpreting ratios leads to qualitative understanding and the development of formal reasoning (6,17), dimensional analysis has been advocated by some for students who are concrete reasoners (23,24 ), and it may have merit when students are involved in timed tests in which speed in obtaining a result is important. Conditions did not lend themselves to controlled experiments (e.g., the number of consecutive days of classroom visits varied with each group owing to other required activities, and some student attendance was erratic), but our experiences suggest that a combination of approaches may work to help students develop problem-solving skills.…”
Section: Engaging High School Students In the Methodsmentioning
confidence: 99%
“…Garrett (1983) has developed a card game as an aid in teaching the factor-label method. Berger (1985, p. 396), suggested that the conversion factors be deduced from a conversion matrix: "equate the number of moles of each species...and write the equivalent number of grams of each species...under its corresponding number of moles."…”
Section: Mol S Atoms = ( 3 Ffr~) X (1 M~ S At~ ~ = 3 Mol S Atoms K]mentioning
confidence: 99%